Ultrafiltration Enhanced with Activated Carbon Adsorption for Efficient Dye Removal from Aqueous Solution - 董亚楠 苏延磊 陈文娟 彭金明 张岩 姜忠义 (Chinese journal of chemical engineering, 2011)
In this study, orange G dye was efficiently removed from aqueous solution by ultraflltration （UF） membrane separation enhanced with activated carbon adsorption. The powdered activated carbon （PAC） was deposited onto the UF membrane surface, forming an intact filter cake. The enhanced UF process simultaneously exploited the high water permeation flux of porous membrane and the high adsorption ability of PAC toward dye molecules. The influencing factors on the dye removal were investigated. The results indicated that with sufficient PAC incorporation, the formation of intact PAC filtration cake led to nearly complete rejection for dye solution under opti-mized dye concentration and operation pressure, without large sacnticlng the permeation tlux ot the filtration process. Typically, the dye rejection ratio increased from 43.6% for single UF without adsorption to nearly 100% for the enhanced UF process, achieving long time continuous treatment with water permeation flux of 47 L·m^-2·h^-1. The present study demonstrated that adsorption enhanced UF may be a feasible method for the dye wastewater treatment.